2019
DOI: 10.37393/jass.2019.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Body Composition of Young Artistic Gymnasts From Bulgaria

Abstract: Young gymnasts should not have excessive body mass because that might lead to underperformance. Therefore, children practising gymnastics should consume a balanced diet, which will promote their physical abilities and optimal body mass. The aim of this study was to compare the nutrient intake of young Bulgarian artistic gymnasts to matched groups from the National Nutrition Survey in Bulgaria (NNSB2003). The study consisted of 76 artistic gymnasts (5 to 14 years of age) from four cities in Bulgaria, and the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Moreover, the mean percentile scores (PRs) of height and %Fat in the gymnasts were also lower than the 50 th percentile of the WHO norms for children at the same age and from the same gender. However, such lower mean values are within the published results in children engaged in gymnastics [6,21,25,31,34]. Although gymnasts are shorter on average and their height-for-age progressively decreases as the age increases [7,25], review on the role of training on the growth of the gymnasts concluded that adult height of artistic gymnasts of both genders is not compromised by intensive gymnastics training at a young age or during the pubertal growth spurt [39].Thus, artistic gymnastics plays an unique role as a sport which provides opportunities for those with smaller body sizes in a world where many sports are biased in favour of tall or big athletes [54].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the mean percentile scores (PRs) of height and %Fat in the gymnasts were also lower than the 50 th percentile of the WHO norms for children at the same age and from the same gender. However, such lower mean values are within the published results in children engaged in gymnastics [6,21,25,31,34]. Although gymnasts are shorter on average and their height-for-age progressively decreases as the age increases [7,25], review on the role of training on the growth of the gymnasts concluded that adult height of artistic gymnasts of both genders is not compromised by intensive gymnastics training at a young age or during the pubertal growth spurt [39].Thus, artistic gymnastics plays an unique role as a sport which provides opportunities for those with smaller body sizes in a world where many sports are biased in favour of tall or big athletes [54].…”
Section: Discussionsupporting
confidence: 83%
“…The food frequency questionnaire (FFQ), which was used in other nutritional surveys on gymnasts 38,39 was applied in this study in order to assess the nutrient intake of the rhythmic gymnasts. This questionnaire consists of questions relating to the weekly consumption of different types of food, in addition to questions about the physical activity and height and weight of the gymnasts.…”
Section: Methodsmentioning
confidence: 99%
“…The food frequency questionnaire (FFQ) [48,49], which was applied in this study to assess the nutrition of the swimmers, included questions about the weekly use of basic food products and questions about the age, sports experience, and number of training sessions per week. The composition and energy value of different groups of food were calculated based on the USDA National Nutrient Database -Release 28 [50].…”
Section: Nutritional Assessmentmentioning
confidence: 99%